Readiness of the Batam City Government in implementing sustainable transportation - Karol Teovani Lodan; Etika Khairina; Timbul Dompak; Lubna Salsabila; Aqil Teguh Fathani (Masyarakat, Kebudayaan dan Politik, 2023)
Batam City transportation has several problems that are influenced by the conditions of the public transportation system. The purpose of this study will be to examine the application of Smart Mobility by the Batam City Government as an effort to realize sustainable transportation in Batam City so that, through this study, an overview of the Batam City Government’s readiness to apply the concept of sustainable (Smart City) will be obtained. This study uses a qualitative analysis research method that begins with a literature review process followed by data collection. The analysis technique used is triangulation supported by data analysis tools, namely VOSviewer and NVivo 12 Plus. The study results show that intelligent mobility in Batam City has not been implemented optimally and has not taken a sustainable approach. This is evidenced by the conclusions of the study which show that there is no balance in applying for development policies/programs in sustainability (economic, social, environmental) and the absence of legal products that focus on the concept of sustainable transportation, as well as the lack of use of information, communication, technology in transportation.